Science communication audiences in Lithuania: science motivation, attitudes toward media, and nature–friendly behavior - Dirzyte, Aiste (Frontiers in Communication, 2025)
Based on prior engagement-based segmentation of science communication audiences, to fill the gap on knowledge about audience segments in a Lithuanian context, this study aimed to explore the groups within society having different levels of trust and interest in science, and to compare them on science motivation, attitudes toward media and nature-friendly behaviors. A representative sample of 1,005 adults, aged 18 and above, with a mean age of 45.1 years (SD = 14.8) participated in the study carried out in 2024. Based on prior research, it was expected that four distinct profiles would emerge, but the LPA revealed just two distinct latent classes within the Lithuanian sample. Higher engagement group, 60.1% of the sample, scored higher on all interest and trust in science indicators, whereas lower engagement group, 39.9% of the sample, showed minor engagement with science. T-test analysis revealed additional differences between the profiles. Firstly, individuals in the higher engagement group were more motivated to learn about science “simply because they find it interesting.” Second, the higher engagement group had more trust in the media’s ability to inform them accurately about science and research. Finally, the findings showed that individuals who are more engaged with science are also more inclined to take environmentally friendly actions.